The Contextualization of Self and Place Within a Second-Grade Study of Recent Immigration. Issue 3 (March 2020) - Shin, Sunghee; Bisland, Beverly Milner (Lee)
Immigration is a public issue that needs student exploration. This cross-disciplinary study brings awareness of diverse cultures by studying immigration through personal history in a multiethnic urban elementary school. Research suggests the importance of integrating assets students bring into the classroom in instruction. Changing pedagogies also emphasize the need for students to participate in community-based inquiries. This asset-based perspective centers students as knowledge producers, instead of knowledge consumers, making them active participants in learning.